Clinical impact of cachexia in unresectable locally advanced head and neck cancer: supplementary analysis of a phase II trial (JCOG0706-S2). (26th October 2018) - Matsuzuka, Takashi; Kiyota, Naomi; Mizusawa, Junki; Akimoto, Tetsuo; Fujii, Masato; Hasegawa, Yasuhisa; Iwae, Shigemichi; Monden, Nobuya; Matsuura, Kazuto; Onozawa, Yusuke; Hayashi, Ryuichi; Tahara, Makoto; et al.
Abstract : In a supplementary analysis of JCOG0706, chemoradiotherapy for head and neck cancer, pretreatment cachexia appears to predict a poor prognosis. Further, results for treatment completeness suggest that is a candidate stratification factor. Abstract: Objectives: To evaluate the clinical impact of cachexia, defined by the combination of albumin and C-reactive protein levels, in patients with unresectable locally advanced head and neck squamous cell carcinomas who received chemoradiotherapy in a phase II trial of JCOG0706. Methods: Forty-five patients received radiation for a total of 70 Gy/35fr concurrently with S-1 and cisplatin. The present analysis was conducted in 44 patients with available data. The association between treatment efficacy and cachexia was investigated. Pretreatment cachexia was defined as a serum albumin level of less than 3.5 mg/dl and C-reactive protein level of more than 0.5 mg/dl. Results: Among the 44 patients, 5 patients had cachexia. On comparison with the cachexic and non-cachexic patients, the percentage of clinical complete remission (20% vs 72%), time to treatment failure at 3 years, (20% vs 53%) and proportion of treatment completion (20% vs 79%) were statistically worse in the cachexic patients, while overall survival, progression-free survival and local progression-free survival at 3 years tended to be worse in cachexic patients. Conclusions: This supplementary analysis from a prospective study suggests that a pretreatment status of cancer cachexia is a prognostic factor for treatment outcomes and compliance in patients with locally advanced head and neck squamous cell carcinomas treated with chemoradiotherapy, and a candidate stratification factor in future prospective trials in this population.